A review of paediatric and adolescent gynaecology services in a tertiary outpatient clinic. (3rd July 2017) - Kulkarni, Mugdha; Glanville, Julie; Phillot, Sally; Balen, Adam
Abstract: Adolescence is a distinctive stage in human development during which many simple and complex medical conditions can present for the first time. Paediatric and adolescent gynaecological conditions need careful multidisciplinary clinical management with a sensitive approach understanding the patients' psychological and physiological circumstances. The objective of this study is to review the tertiary paediatric and adolescent gynaecology service in Leeds, United Kingdom and to present an overview of the various conditions that present to such a clinic. A total of 985 patients were seen over a 16-year period and the increasing number of patients seen over this time establishes the need for such a service to exist. Complex developmental anomalies of the genital tract and disorders of sexual differentiation formed a major portion of the referrals. Presence of a significant number of referrals for simple gynaecological conditions including menstrual irregularities, gynaecological pain, vulvovaginitis, polycystic ovary syndrome and concerns about labial appearance indicates the reluctance of general gynaecologists and general practitioners to manage such conditions in young patients. This emphasizes the need for continued education of primary health care professionals and establishment of clear guidelines and care pathways for the management of this special patient group.